Roles of Macrophages and Exosomes in Liver Diseases - Shen, Mengyi; Shen, Yi; Fan, Xiaoli; Men, Ruoting; Ye, Tinghong; Yang, Li (Frontiers in Medicine, 2020)
Exosomes are small discoid extracellular vesicles (EVs) originating from endosomes that are approximately 30-150 nm in diameter and have a double lipid layer. They participate in the immune response, cell migration, cell differentiation, and tumor invasion and mediate intercellular communication, regulating the biological activity of receptor cells through the proteins, nucleic acids and lipids that they carry. Exosomes also play vital roles in the diagnosis and treatment of liver diseases. Macrophages, which show unique phenotypes and functions in complex microenvironments, can be divided into M1 and M2 subtypes. M1 macrophages function in immune surveillance, and M2 macrophages downregulate the immune response. Recent studies have shown that macrophages are involved in nonalcoholic fatty liver disease, liver fibrosis, and hepatocellular carcinoma. Moreover, several studies have demonstrated that liver diseases are associated with exosomes derived from or transferred to macrophages. This review focuses on the participation of macrophages and exosomes in liver diseases.